Legal analysis of land ownership disputes: a case study of Banda Aceh high court decision No. 114/Pdt/2023/PT BNA - Mutia, Najwa; Khairani, K (Geuthèë Institute, Aceh, 2025)
Inheritance-related land ownership disputes frequently arise due to insufficient evidentiary proof of land ownership rights. This study examines a land dispute in the Banda Aceh High Court Decision Number 114/Pdt/2023/PT BNA, as amended by the Supreme Court Decision Number 4088 K/Pdt/2024, with a focus on the judges’ legal reasoning and the application of the principles of legal certainty and justice. The research employs a normative juridical approach, using a case study to analyze statutory regulations, court decisions, and legal doctrines. The findings reveal that the panel of judges validated a deed of separation and inheritance distribution executed under private hand, without satisfying the requirements of Article 51, paragraph (1), and Article 37, paragraph (1), of Government Regulation Number 24 of 1997 on Land Registration. The decision is considered to lack legal certainty and fails to demonstrate the consistent application of legal norms in accordance with Hans Kelsen’s concept of justice. Therefore, resolving inheritance land disputes requires a balance between legal certainty and justice to ensure optimal legal protection for the parties involved.